The effects of portfolios on the writing accuracy of 10th graders at An Minh High school in Kien Giang province - Đinh Việt Đoàn (Trường Đại học Trà Vinh, 2020)
Given the downsides of traditional assessment approach at An Minh High School in Kien Giang Province, the researcher decided to conduct a study on the relationship of portfolios and students’ writing accuracy. Thus the study aims to investigate the effects of a portfolio on students’ writing accuracy. It is composed of two objectives: It tries to find out whether the introduction of a portfolio can enhance students’ writing and what they think about this treatm ent.